THE INFLUENCE OF PRODUCT QUALITY AND PRODUCT PRICES ON THE PURCHASE OF TUNAS BANANA CHIPS AT METRO CITY - Anggi Bayu A; Ery Baskoro (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
In companies engaged in retail sales, strategies are needed to increase consumer buying interest. One way to increase consumer buying interest is to improve product quality and competitive prices. The purpose of this study was to determine the effect of product quality and product prices on purchasing Metro Tunas Banana Chips City. The method used in this research is the explanatory survey method. This type of research is quantitative and qualitative research with the object of research is product quality, product prices and purchases. The study population is the Home Industry Metro City Tunas Banana Chips consumers with a number of samples taken as many as 75 respondents. Data collection techniques using questionnaires. The analytical tool used is multiple linear regression analysis. The results showed that the quality of the product had a significant effect on purchases. Product prices have a significant effect on purchases. Product quality and product prices simultaneously have a significant effect on purchases. Based on the coefficient number and the calculated value, it can be seen that the most influential factor on purchasing is product quality.